Synthesis Report on Five-Country Institutional Analysis Produced for the CIAT Scoping Study on Soil Research and Management to Enrich Bilateral German Development Cooperation Programs - Snyder, Katherine A.; Okolo, Wendy; Sommer, Rolf; Braslow, Juliet (2015)
The Scoping Study on Soil Research and Management to Enrich Bilateral German Development Cooperation Programs, conducted by the International Center for Tropical Agriculture (CIAT) and funded by the German Federal Ministry for Economic Cooperation and Development (BMZ) with support from the German Agency for International Cooperation (GIZ-GmbH), aimed to ensure that the current state of the art of soil research is reflected in the Soil Protection and Rehabilitation for Food Security initiative of BMZ/GIZ, and to enrich new GIZ (country) projects with information on how best to revitalize soils and help positioning new efforts within national (institutional) frameworks. This synthesis report reflects institutional analyses of five prioritized countries: Benin, Burkina Faso, Ethiopia, India, and Kenya.